High-Performance Liquid Chromatography Determination of Propranolol in Human Plasma - T. Baviskar, Dheeraj; P. Pawar, Mahesh; S. Kale, Sachin; D. Jain, Paridhi; K. Jain, Dinesh (Asian Journal of Chemistry, 2011)
A simple rapid, selective sensitive and novel high pressure liquid chromatographic (HPLC) method was developed and validated for the assay of propranolol. Sample preparation was performed by liquid-liquid extraction in ethyl acetate. The organic solvent was evaporated and the residue dissolved in a mobile phase. Aliquots of 60 μL were injected automatically into the chromatograph. The separation of propranolol was achieved on a reversed phase C18 column with a mobile phase consisting of 10 mM ammonium acetate, acetonitrile,: TEA (70:30:0.01 v/ v/v). Quantitation of propranolol was performed by UV detection at 210 nm. The linearity range was 5 to 80 ng/mL. Inter-day and intra day accuracy and precision was found 91.26-109.13, 2.79-5.79 and 92.15-108.52, 1.52-5.67 respectively. Long term stability for 30 days of propranolol in human plasma was proved as per guidelines.